Visualisation, 3D Modelling and Spatial Analysis of the Rustenburg Layered Suite, Bushveld Igneous Complex, South Africa - Van Rooy, J.L. (Jan Louis) (University of Pretoria, 2018)
Thesis (PhD)--University of Pretoria, 2015.